BETTING IN CYBERSPACE: A STUDY OF THE CURRENT LITERATURE ON THE PSYCHOSOCIAL IMPACT OF ONLINE GAMBLING - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
Online gambling has become a rapidly growing global phenomenon, raising concerns about its psychosocial impact on individuals and society. The method used in this study utilized literature. The study results show that online gambling has significant potential negative impacts, including increased risk of addiction, financial problems, impaired social relationships, and various mental health problems. However, the impact varies depending on individual and contextual factors. The ease of access and special features of online platforms were found to contribute to the increased risk of problematic gambling behavior.